Method for preparing self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering
By using a corrosion-coordination engineering method to prepare a nanoparticle free-standing hydrogen evolution catalyst on a foam iron substrate, the problem of large hydrogen evolution reaction barrier in electrolyzing water to produce hydrogen is solved, and high-efficiency electrocatalytic hydrogen evolution performance and low cost are achieved. Utilization of precious metals.
Patent Information
- Application Number
- CN202210982659.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-08-16
AI Technical Summary
During the existing process of electrolyzing water to produce hydrogen, the hydrogen evolution reaction has a high reaction potential barrier, which leads to excessive electrical energy loss. It is urgent to develop a high-efficiency hydrogen evolution catalyst to improve the reaction kinetics and overpotentials.
Using a method based on corrosion-coordination engineering, foam iron is used as the substrate, and a mixed solution of RuCl3 and sodium gluconate is soaked on it. An active corrosion layer is grown in situ through the metal spontaneous corrosion process, and the Ru metal is evenly loaded to prepare nanoparticles. Free-standing hydrogen evolution catalyst.
The prepared catalyst has excellent electrocatalytic hydrogen evolution performance and can reach a current density of 100mA cm-2 with only 90~110mV overpotential in 1mol L-1KOH solution, which significantly improves the catalytic activity and reduces the usage of precious metals.
Smart Images

Figure CN115386896B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of hydrogen evolution catalysts by electrolysis of water, and particularly relates to a method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering. Background Art
[0002] Hydrogen energy is a renewable energy source with high-quality energy density, clean and pollution-free, and rich application scenarios. It can well replace traditional energy. Producing hydrogen by electrolysis of water is an important direction for the development of hydrogen production technology in the future. However, one of the two half reactions of water electrolysis, the hydrogen evolution reaction (HER), has a high reaction barrier during the electrolysis process. In order to avoid excessive power loss during the electrolysis process, it is urgent to develop efficient hydrogen evolution catalysts to improve the sluggish reaction kinetics and high reaction overpotential of HER.
[0003] Precious metals (Pt, Ir, Ru, etc.) have moderate hydrogen adsorption and desorption kinetics and are ideal HER catalysts. Compared with other precious metals, Ru has a greater cost advantage, but it is still limited by the low reserves of precious metals and is difficult to apply on a large scale. How to reduce the use of precious metals while ensuring catalytic activity is an important way to improve the utilization rate of precious metals. Foam metals have a three-dimensional porous structure, showing the characteristics of high specific surface area, high conductivity, and easy adsorption of reactants. They are excellent self-supporting substrate materials. Loading precious metals on them can greatly reduce the use of precious metals and prepare self-supporting hydrogen evolution catalysts with high activity, high stability, and low cost. The preparation process of traditional self-supporting hydrogen evolution catalysts is cumbersome, the production cost is high, and it is not conducive to regulating the structure and performance of the catalyst. The metal corrosion strategy uses the spontaneous corrosion behavior of metals to prepare catalysts, which can solve the above problems well. This method is simple in process, green and environmentally friendly, easy to control, and is expected to achieve large-scale production. The present invention uses foamed iron as a substrate, and controls the corrosion process of RuCl3 on the foamed iron by adding sodium gluconate, so as to uniformly load the precious metal Ru on the foamed iron substrate, thereby preparing a self-supporting hydrogen evolution catalyst with excellent electrocatalytic activity. Currently, there is no relevant literature reporting on this aspect. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering with simple process and low cost. The method utilizes the spontaneous corrosion process of metal, immerses foamed iron in a RuCl3 / sodium gluconate mixed solution, and in-situ grows an active corrosion layer on the foamed iron substrate, wherein the sodium gluconate can compete with chloride ions in a ruthenium chloride solution to be adsorbed onto the surface of the foamed iron, and at the same time, the carboxyl groups in the gluconate radicals can combine and coordinate with the ruthenium ions, thereby reducing the corrosion effects of the chloride ions and the ruthenium ions and promoting the uniform growth of the active corrosion layer. The self-supporting hydrogen evolution reaction catalyst finally prepared has a nano-particle morphology, can provide abundant active sites, and is conducive to the progress of the electrocatalytic hydrogen evolution reaction.
[0005] The present invention adopts the following technical solution to solve the above technical problems, and is a method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering, which is characterized by the specific process of:
[0006] Step S1: immersing the foamed iron in anhydrous ethanol for ultrasonic cleaning to remove organic pollutants on the surface of the foamed iron, then immersing the foamed iron in dilute hydrochloric acid for ultrasonic cleaning to remove oxides on the surface of the foamed iron, and after the ultrasonic cleaning, washing the foamed iron with deionized water and anhydrous ethanol in sequence to remove residual acidic substances, thereby obtaining material A;
[0007] Step S2: adding sodium gluconate to deionized water and stirring, adding ruthenium chloride solution after thorough mixing, and stirring to obtain a uniformly mixed solution B, wherein the molar concentrations of sodium gluconate and ruthenium chloride in the solution B are 0.5-2 mM and 1-3 mM, respectively;
[0008] Step S3: adding the material A obtained in step S1 to the solution B obtained in step S2, and stirring at room temperature to allow the material A and the solution B to fully react to obtain a material C, wherein the material A serves as a self-supporting substrate;
[0009] Step S4: Wash the material C obtained in step S3 with deionized water and anhydrous ethanol, and then dry it in a forced air drying oven at 80° C. to finally obtain the target product, a self-supporting hydrogen evolution reaction catalyst.
[0010] Further preferably, the size of the foam iron in step S1 is 1 to 9 cm 2 .
[0011] More preferably, the rotation speed of the magnetic stirrer in step S3 is 100-200 rpm.
[0012] Further preferably, the self-supporting hydrogen evolution electrocatalyst in step S4 is -1 In KOH solution, only 90~110mV overpotential is required to reach 100mA cm -2 Current density, with excellent electrocatalytic hydrogen evolution performance.
[0013] Further preferably, the method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering is characterized by the specific steps of:
[0014] Step S1: ultrasonically treat the foamed iron with anhydrous ethanol for 3-5 minutes; then ultrasonically clean it with dilute hydrochloric acid for 60-80 minutes, and finally rinse it with deionized water and anhydrous ethanol to obtain material A1;
[0015] Step S2: adding sodium gluconate to 30 mL of deionized water, stirring for 30 min, adding ruthenium trichloride, and stirring for another 60 min to obtain a solution B1, wherein the molar concentration of sodium gluconate is 1 mM, and the molar concentration of ruthenium trichloride is 2 mM;
[0016] Step S3: adding the material A1 obtained in step S1 to the solution B1 obtained in step S2, and stirring at room temperature for 60 minutes to allow the material A1 and the solution B1 to fully react to obtain the material C1, wherein the material A1 serves as a self-supporting substrate;
[0017] Step S4: The material C1 obtained in step S3 is washed with deionized water and anhydrous ethanol, and then placed in an 80° C. forced air drying oven for 2 h to obtain the target product, a self-supporting hydrogen evolution reaction catalyst.
[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0019] 1. The present invention utilizes the spontaneous corrosion process of metals. Under room temperature conditions, the foamed iron is immersed in a mixed solution of RuCl3 / sodium gluconate to in-situ grow a nano-granular active corrosion layer on the foamed iron substrate, which can provide abundant active sites for the electrocatalytic reaction process;
[0020] 2. The present invention adds an appropriate concentration of sodium gluconate, and the gluconate ions and chloride ions in the solution have a competitive adsorption relationship, which can hinder the accelerated corrosion of chloride ions. At the same time, the carboxyl groups in the gluconate ions will combine and coordinate with the ruthenium ions to slow down the corrosion ability of the ruthenium ions. When the concentration is too high or too low, it affects the morphology of the catalyst and then affects the activity of the catalyst. Sodium gluconate at a specific concentration has a suitable competitive adsorption rate and coordination ability, which can promote the uniform growth of the nano-granular active corrosion layer, improve the accessibility of the active sites, and thus significantly improve the catalytic activity.
[0021] 3. The self-supporting hydrogen evolution electrocatalyst prepared by the present invention has a -1 In KOH solution, only 90~110mV overpotential is required to reach 100mA cm -2 Current density, with excellent electrocatalytic hydrogen evolution performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the target product D1 prepared in Example 1;
[0023] Figure 2 The electrochemical impedance spectroscopy diagram of the target product D1-D2 prepared in Example 1-2;
[0024] Figure 3 The linear sweep voltammetry curves of target products D1-D4 prepared in Examples 1-4;
[0025] Figure 4 Corrosion polarization curves of target products D1-D4 prepared in Examples 1-4. DETAILED DESCRIPTION
[0026] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0027] Example 1
[0028] Step S1: using anhydrous ethanol to ultrasonically treat the foamed iron for 4 minutes; then using dilute hydrochloric acid to ultrasonically clean for 60 minutes, and finally using deionized water and anhydrous ethanol to rinse, to obtain material A1;
[0029] Step S2: adding sodium gluconate to 30 mL of deionized water, stirring for 30 min, adding ruthenium trichloride, and stirring for another 60 min to obtain a solution B1, wherein the molar concentration of sodium gluconate is 1 mM, and the molar concentration of ruthenium trichloride is 2 mM;
[0030] Step S3: adding the material A1 obtained in step S1 to the solution B1 obtained in step S2, and stirring at room temperature for 60 minutes to allow the material A1 and the solution B1 to fully react to obtain the material C1, wherein the material A1 serves as a self-supporting substrate;
[0031] Step S4: The material C1 obtained in step S3 is washed with deionized water and anhydrous ethanol, and then placed in an 80° C. forced air drying oven for 2 h to obtain the target product D1.
[0032] Example 2
[0033] Step S1: ultrasonically treat the foamed iron with anhydrous ethanol for 4 minutes; then ultrasonically clean it with dilute hydrochloric acid for 60 minutes, and finally rinse it with deionized water and anhydrous ethanol to obtain material A2;
[0034] Step S2: adding the ruthenium trichloride solution to 30 mL of deionized water and stirring for 60 min to obtain a solution B2, wherein the molar concentration of ruthenium trichloride is 2 mM;
[0035] Step S3: adding the material A2 obtained in step S1 to the solution B2, and stirring at room temperature for 60 minutes to allow the material A2 and the solution B2 to fully react to obtain the material C2, wherein the material A2 serves as a self-supporting substrate;
[0036] Step S4: The material C2 obtained in step S3 is washed with deionized water and anhydrous ethanol, and then placed in an 80° C. forced air drying oven for 2 h to obtain the target product D2.
[0037] Example 3
[0038] Step S1: ultrasonically treat the foamed iron with anhydrous ethanol for 4 minutes; then ultrasonically clean it with dilute hydrochloric acid for 60 minutes, and finally rinse it with deionized water and anhydrous ethanol to obtain material A3;
[0039] Step S2: adding sodium gluconate to 30 mL of deionized water, stirring for 30 min, adding ruthenium trichloride, and stirring for another 60 min to obtain solution B3, wherein the molar concentration of sodium gluconate is 0.1 mM, and the molar concentration of ruthenium trichloride is 2 mM;
[0040] Step S3: adding the material A3 obtained in step S1 to the solution B3 obtained in step S2, and stirring at room temperature for 60 min to allow the material A3 and the solution B3 to fully react to obtain material C3, wherein the material A3 serves as a self-supporting substrate;
[0041] Step S4: The material C3 obtained in step S3 is washed with deionized water and anhydrous ethanol, and then placed in an 80° C. forced air drying oven for 2 h to obtain the target product D3.
[0042] Example 4
[0043] Step S1: ultrasonically treat the foamed iron with anhydrous ethanol for 4 minutes; then ultrasonically clean it with dilute hydrochloric acid for 60 minutes, and finally rinse it with deionized water and anhydrous ethanol to obtain material A4;
[0044] Step S2: adding sodium gluconate to 30 mL of deionized water, stirring for 30 min, adding ruthenium trichloride, and stirring for another 60 min to obtain a solution B4, wherein the molar concentration of sodium gluconate is 5 mM, and the molar concentration of ruthenium trichloride is 2 mM;
[0045] Step S3: adding the material A4 obtained in step S1 to the solution B4 obtained in step S2, and stirring at room temperature for 60 minutes to allow the material A4 and the solution B4 to fully react to obtain material C4, wherein the material A4 serves as a self-supporting substrate;
[0046] Step S4: The material C4 obtained in step S3 is washed with deionized water and anhydrous ethanol, and then placed in an 80° C. forced air drying oven for 2 h to obtain the target product D4.
[0047] Example 5
[0048] Cut 0.5×1cm 2 The target product D1 was fixed with a platinum electrode clamp as the working electrode (effective area 0.5 × 0.4 cm 2 ), the same method was used to prepare the working electrodes of the target products D2, D3, and D4 as the control group of the target product D1. All electrochemical tests used a three-electrode system, and the electrolyte was 1 mol L -1 The KOH solution was used as the reference electrode and the carbon rod was used as the counter electrode. The scanning rate of the linear sweep voltammetry (LSV) test was 5 mV s -1 , the scanning range is 0~-0.4V (vs. RHE).
[0049] The performance characteristics of the target products in all embodiments are as follows: Figure 1 As shown, it is a scanning electron microscope image of the target product D1 prepared in Example 1. The prepared target product has a clear nano-particle structure. Figure 2 The electrochemical impedance diagram of the target product D1-D2 prepared in Example 1-2 shows that the radius of product D1 is significantly smaller than that of D2, indicating that product D1 has better charge transfer ability. Figure 3 The linear sweep voltammetric curves of the target products D1-D4 prepared in Examples 1-4 are shown at 100 mA cm -2 Under current density, as the concentration of sodium gluconate in the solution increases, the overpotentials of the products D2, D3, D1 and D4 are 166mV, 102mV, 94mV and 123mV respectively, and the overpotential reaches the minimum at D1. The above results show that the target product D1 has good electrochemical hydrogen evolution performance. Figure 4 The corrosion polarization curves of the target products D1-D4 prepared in Examples 1-4 show that the corrosion degree of the target product D1 is between D3 and D4, indicating that the corrosion rate of the target product D1 can better promote the growth of a uniform active corrosion layer.
[0050] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering, characterized in that The specific process is: Step S1: immersing the foamed iron in anhydrous ethanol for ultrasonic cleaning to remove organic pollutants on the surface of the foamed iron, then immersing the foamed iron in dilute hydrochloric acid for ultrasonic cleaning to remove oxides on the surface of the foamed iron, and after the ultrasonic cleaning, washing the foamed iron with deionized water and anhydrous ethanol in sequence to remove residual acidic substances, thereby obtaining material A; Step S2: adding sodium gluconate to deionized water and stirring, adding ruthenium chloride solution after thorough mixing, and stirring to obtain a uniformly mixed solution B, wherein the molar concentrations of sodium gluconate and ruthenium chloride in the solution B are 0.5-2 mM and 1-3 mM, respectively; Step S3: adding the material A obtained in step S1 to the solution B obtained in step S2, and stirring at room temperature to allow the material A and the solution B to fully react to obtain a material C, wherein the material A serves as a self-supporting substrate; Step S4: Wash the material C obtained in step S3 with deionized water and anhydrous ethanol, and then dry it in a forced air drying oven at 80° C. to finally obtain the target product, a self-supporting hydrogen evolution reaction catalyst.
2. The method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering according to claim 1, characterized in that: The size of the foam iron in step S1 is 1~9cm 2 .
3. The method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering according to claim 1, characterized in that: The stirring speed in step S3 is 100-200 rpm.
4. The method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering according to claim 1, characterized in that: The self-supporting hydrogen evolution electrocatalyst in step S4 is 1 mol L -1 In KOH solution, only 90~110mV overpotential is required to reach 100mA cm -2 Current density, with excellent electrocatalytic hydrogen evolution performance.
5. The method for preparing a self-supporting hydrogen evolution reaction catalyst based on corrosion-coordination engineering according to claim 1, characterized in that The specific steps are: Step S1: ultrasonically treat the foamed iron with anhydrous ethanol for 3-5 minutes; then ultrasonically clean it with dilute hydrochloric acid for 60-80 minutes, and finally rinse it with deionized water and anhydrous ethanol to obtain material A1; Step S2: adding sodium gluconate to 30 mL of deionized water, stirring for 30 min, adding ruthenium trichloride, and stirring for another 60 min to obtain a solution B1, wherein the molar concentration of sodium gluconate is 1 mM, and the molar concentration of ruthenium trichloride is 2 mM; Step S3: adding the material A1 obtained in step S1 to the solution B1 obtained in step S2, and stirring at room temperature for 60 minutes to allow the material A1 and the solution B1 to fully react to obtain the material C1, wherein the material A1 serves as a self-supporting substrate; Step S4: The material C1 obtained in step S3 is washed with deionized water and anhydrous ethanol, and then placed in an 80° C. forced air drying oven for 2 h to obtain the target product, a self-supporting hydrogen evolution reaction catalyst.